2015
DOI: 10.1007/s40263-015-0231-5
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin–Norepinephrine Reuptake Inhibitor and Selective Serotonin Reuptake Inhibitor Use and Risk of Fractures: A New-User Cohort Study Among US Adults Aged 50 Years and Older

Abstract: Background Antidepressants may increase the risk of fractures by disrupting sensory-motor function, thereby increasing the risk of falls, and by decreasing bone mineral density and consequently increasing the fall- or impact-related risk of fracture. Selective serotonin reuptake inhibitor (SSRI) antidepressants appear to increase fracture risk relative to no treatment, while less is known about the effect of serotonin-norepinephrine reuptake inhibitor (SNRI) antidepressants, despite SNRIs being prescribed with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 21 publications
(36 reference statements)
1
32
0
1
Order By: Relevance
“…The mechanism of action of different classes of antidepressants appears to produce different skeletal effects: several rodent and human observational studies have reported negative skeletal effects with serotonergic antidepressants. There have been several recent studies linking SSRI/SNRI drugs to increased fragility in humans, which are consistent with our results (Warden et al, 2010(Warden et al, , 2008Bonnet et al, 2007;Lanteigne et al 2015;Moura et al, 2014).…”
Section: Discussionsupporting
confidence: 93%
“…The mechanism of action of different classes of antidepressants appears to produce different skeletal effects: several rodent and human observational studies have reported negative skeletal effects with serotonergic antidepressants. There have been several recent studies linking SSRI/SNRI drugs to increased fragility in humans, which are consistent with our results (Warden et al, 2010(Warden et al, , 2008Bonnet et al, 2007;Lanteigne et al 2015;Moura et al, 2014).…”
Section: Discussionsupporting
confidence: 93%
“…No relevant randomized controlled studies were found. Sixteen studies were included from the previous systematic review, and 17 studies were identified as new in the databases (Figure ) …”
Section: Resultsmentioning
confidence: 99%
“…The studies we found were published between 1998 and 2016, with 11 studies since 2013 . Two studies were reported across multiple articles and each was treated as a single distinct study: Vestergaard et al and Souverein et al One study reported results from both a cohort and a nested case‐control analysis .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Antidepressants, and particularly selective serotonin reuptake inhibitors (SSRI), can have negative effects on the bone and increase the risk of fractures 122,123 . Depression is also one of the strongest risk factors for revision in arthroplasty patients 72 .…”
Section: Medicationsmentioning
confidence: 99%